Incidence of Post-operative Pulmonary Complications Following Cytoreductive Surgeries and HIPEC- A Retrospective Analytic Study - Roopesh Sureshan; Satheesan B; Sonali Opneja; Jashma C; Joona P; Namratha Divakaran; Mayan John (Asian Pacific Journal of Cancer Care, 2023)
Background and aims: Cytoreductive surgery (CRS) is performed to treat macroscopic disease and Hyperthermic intraperitoneal chemotherapy (HIPEC) is used to treat the microscopic residual disease. Abdominal surgeries are sometimes associated with pulmonary complications and also prolonged hospital stays. The aim of this retrospective study was to determine the incidence of post-operative pulmonary complications occurring within 30 days following CRS and HIPEC. The risk factors responsible were also identified. Materials and methods: The retrospective study was done in patients who underwent CRS and HIPEC. Patient’s data was retrieved from 31st May 2018 to 30th June 2022. The data was obtained from the patient records and registers kept in the medical records library. Post operative pulmonary complications were noted and risk factors were identified. Results: There were 27 surgeries of CRS with HIPEC during the study period.The procedure was done in patients with the primary tumour of ovary, colon, appendix, ewings sarcoma pelvis and peritoneum. 6 patients developed post operative pulmonary complications. The complications included pleural effusion in 4 patients and acute respiratory distress syndrome (ARDS) in 2 patients. Conclusion: The incidence of postoperative pulmonary complications in our study was 22 % following CRS and HIPEC. Pleural effusion was the common complication noted, followed by (ARDS). The intrinsic disease in association with hypoalbuminemia (< 2gm/dl) was found to be an important factor for causing pleural effusion.